(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Pneumothorax (PTX) is a life-threatening condition that overdiagnosis could result in increases in mortality and morbidity of patients. A-71-year old man was admitted due to multiple trauma. In the examination, there were some abrasions all over his body including his thorax. There were no decreases in respiratory sounds in auscultation but he had little right hemithorax rib tenderness. In his CXR, there was a suspected pleural visceral line. Due to the inconsistency in physical exam and radiologic findings we decided to take a chest CT-scan before the insertion of the chest tube that indicated no PTX for him and the suspected visceral line was skin fold of a permacath for hemodialysis. Several conditions could mimic findings of PTX in CXR that every physician should know and pay attention to them besides special attention to the history taking and physical examination to reduce the morbidity of patients.